EDUKASI SEPUTAR PENYAKIT TIDAK MENULAR PADA MAHASISWA PROGRAM STUDI ILMU KESEHATAN MASYARAKAT FKIK UNIVERSITAS JAMBI - Mekarisce, Arnild Augina; Ningsih, Vinna Rahayu; Tarawifa, Susan (Jurnal Salam Sehat Masyarakat (JSSM), 2024)
Non-communicable diseases (NCDs) are preventable and their risk factors can be controlled. However, most of the behaviors that are at risk of NCDs are often unaware of it. Based on preliminary studies on 259 students of the Public Health Science Study Program (Prodi IKM), it is known that students have never conducted basic routine examinations at least once a year (16.3%) and students do not know the concept of "CERDIK BEHAVIOR" (20.5%). This service aims to increase students' understanding of NCDs and determine the results of early detection of NCD risk. This community service program was carried out in the form of education on the importance of preventing and overcoming NCDs along with the detection of NCD risks, which was attended by 84 students of the public health science study program. Based on the pre-test results, the average reached 63% of correct questions, then increased to 74% in the post-test. Based on anthropometric data and blood pressure measurements, it is known that most have indications of normal body mass index (72.61%), thin (4.76%), very thin (5.95%), mild obesity (10.71%), and severe obesity (5.95%). In addition, most participants had normal blood pressure (64.29%), compared to pre-hypertension (27.38%), and grade 1 hypertension (8.33%). It is hoped that the examination of health conditions in S-1 SMI students will be carried out on an ongoing basis at least once every 6-12 months so that health status and efforts to improve it are known.